The Justinianic church on Jebel Musa, Sinai – Investigation of the seismic behavior of its structural system and interpretation of its destruction mechanism. (September 2022) - Koufopoulos, Petros; Myriantheos, Marina; Miltiadou-Fezans, Androniki; Vrouva, Antigone; Dasiou, Maria-Eleni
Abstract: The Byzantine remains of the three-aisled Basilica with a narthex on Jebel Musa, South Sinai, were known to the scholarly world since the 19th century. The architectural survey of the site (1995) and the excavations of the Hellenic Archaeological Mission at South Sinai (1998–9, 2008) identified additional original parts of the church and unearthed its foundations. This project aimed at first in a more detailed study of the documentation material produced onsite, that includes the detailed survey of the in situ preserved parts of the building and of numerous carved granite architectural members scattered in the surroundings. The outcome of this endeavor is a quite precise graphic reconstruction of the original form of the Basilica and a better understanding of its structure and its constructional characteristics. Moreover, this detailed documentation was further elaborated from the structural point of view with the aim (i) to assume the weaknesses and inherent vulnerabilities of the original structure of the basilica and (ii) to examine various possible failure mechanisms that could provoke the destruction of the monument, taking into account permanent loads and seismic actions. For this purpose, based on the graphic reconstruction, a detailed 3D cad model of the structure was first developed. Subsequently, a preliminary numerical linear elastic analysis was carried out, focusing on the structural behavior under seismic actions. The qualitative evaluation of the analyses results in comparison with the actual remains of the basilica led to a first approximation of the possible failure mechanisms. Highlights: Graphic reconstruction of the Byzantine three-aisled Basilica with a narthex, built by emperor Justinian on Jebel Musa, South Sinai based on bibliographic research, surveys of existing structures, ruins and scattered blocks, along with the finds unearthed by the Hellenic Archaeological Mission's excavations. Identification of the weaknesses and inherent vulnerabilities of the original structure of the basilica. Examination of the various possible failure mechanisms that led to the destruction of the monument. Detailed models of the graphic reconstruction were developed. A qualitative evaluation of data followed, leading to an approximation of the possible failure mechanisms. Subsequently, numerical linear and non-linear comparative analyses were carried out.